Genotypic analysis of Helicobacter pylori by Multiple-Locus Variable-Number TandemRepeats method in southern Brazil - Priscila Cristina Bartolomeu Halicki; Ivy Bastos Ramis; Júlia Silveira Vianna; Thaísa Bozzetti Gautério; Andrea von Groll; Pedro Eduardo Almeida Silva (Universidade de Santa Cruz do Sul, 2016)
Background and objectives: Despite its use as a genotyping method for different microorganisms, few studies have reported the use of Multiple-Locus Variable Number of Tandem Repeats Analysis (MLVA) for the analysis of the clonal diversity of Helicobacter pylori. The aim of this study was to determine the genetic variability of H. pylori strains by MLVA in southern Brazil. Methods: 95 H. pylori DNA samples were obtained from the gastric biopsies of H. pylori-positive patients from two cities in southern Brazil and their clonal analysis was evaluated by MLVA method using electrophoresis in agarose gel. For selection of loci to be analyzed in this study, an in silico analysis of 12 loci previously described in the literature was performed. Results: From the in silico analysis, only four loci were viable for the genotypic analysis of these H. pylori strains, resulting in 90 strains distributed in eight different groups and five orphan strains. Conclusion: Despite MLVA method allow make inferences about the genotypic diversity of a population, our results showed that H. pylori genotyping methods should be critically evaluated prior to their use in this region of Brazil.